MUSIK DANGDUT SAMPAI KE JEPANG - , WIDODO AGUNG NUGROHO; , Stedi Wardoyo ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final project is about Indonesian culture that expanded to Japan, with title Dangdut Music Goes To Jepang. In writing this final project, the writer use data collection techniques by interview with respondents, literature, and articles from the internet. According to the data that already collected by the writer, Dangdut music has expanded in many overseas, especially in Japan. Japanese people look enthusiastic about Dangdut music. That is seen from the O.M RANEMA. OM RANEMA has made a masterpiece Dangdut. Moreover, there is a group Dangdut named KANSAI. The group leader of KANSAI is Mr. Aki Adishakti and this group has experience performing together with the Japanese people.